Pencapaian Kemampuan Berpikir Kritis Matematis Siswa Kelas VII pada Materi Segiempat dengan Strategi Heuristik Krulik-Rudnick - Nisrina Hani Prasetyo; Dori Lukman Hakim (Peneliti.net, 2022)
The purpose of this study was to see whether the achievement of students' mathematical critical thinking skills using the Krulik-Rudnick Heuristic strategy was better than students using conventional learning. This study uses a quantitative approach with a quasi-experimental method. The subjects in this study were 28 students of class VII B and 21 students of class VII D in one of the Bekasi district schools. The critical thinking ability test instrument is in the form of five descriptive questions about quadrilateral material which contains indicators of mathematical critical thinking ability, provides simple explanations, basic skills, concludes, makes further explanations, as well as strategies and tactics. The data collection technique was carried out by providing teaching materials in the form of LKPD to each group, giving a mathematical critical thinking ability test before being given treatment (pretest) and after (posttest). The results of the study stated that the achievement of students' mathematical critical thinking skills using the Krulik-Rudnick Heuristic strategy was better than students using conventional learning.